2001
DOI: 10.1023/a:1011003030287
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Increasing evidence suggests that Fatty acid ethyl esters (FAEE) play a central role in ethanol induced organ damage. In the current study we measured FAEE formation in rats after short-term oral administration of ethanol, in the presence and absence of pre-treatment with acetyl-L-carnitine. Ethanol treatment caused a significant increase in the levels of FAEE, particularly in the brain and heart, but also in the kidney and liver. Increases in FAEE were associated with a significant increase in FAEE synthase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Furthermore, in this study, an increase in the Acetyl-lcarnitine metabolite was observed in response to EP+YG supplementation. The role of Acetyl-l-carnitine in transferring long-chain fatty acids into the mitochondria for b-oxidation have been recognized (67). The data further reinforced the lipid metabolism modulator effects of EP+YG supplementation.…”
Section: Figure 13mentioning
confidence: 78%
“…Furthermore, in this study, an increase in the Acetyl-lcarnitine metabolite was observed in response to EP+YG supplementation. The role of Acetyl-l-carnitine in transferring long-chain fatty acids into the mitochondria for b-oxidation have been recognized (67). The data further reinforced the lipid metabolism modulator effects of EP+YG supplementation.…”
Section: Figure 13mentioning
confidence: 78%
“…Cytokines were shown to inhibit astrocytic glutamate uptake in a dose-dependent manner (Hu, Sheng et al 2000). Utilization of the antioxidant, acetyl-L-carnitine (ALC), prevented ethanol-induced brain toxicity and lipid hydroperoxide levels, indicating important role for ALC in the prevention of alcohol-induced cellular damage (Calabrese, Scapagnini et al 2001; Calabrese, Scapagnini et al 2002). Furthermore, ALC treatment significantly reduced the signs of alcohol withdrawal syndrome and the level of ethanol intake in alcohol-preferring rats (Mangano, Clementi et al 2000).…”
Section: Glutamate and Alcohol Effects In The Cnsmentioning
confidence: 99%
“…These two natural acids are effective in reducing inflammation which may contribute to asthma, liver disease and heart disease [19]. According to other researchers, Rosemary extract protects the individual components of skin cells, which may prevent age-related skin damage such as wrinkles [20]. Another benefit of Rosemary extract has been shown to be the ability to inactivate toxins and then eliminate them from the liver, before they can inflict any serious damage [21], thus stimulating the liver to work more efficiently.…”
Section: Introductionmentioning
confidence: 99%